2022
DOI: 10.1029/2022je007194
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Science and Engineering Questions in Planetary Cave Exploration

Abstract: Nearly half a century ago, two papers postulated the likelihood of lunar lava tube caves using mathematical models. Today, armed with an array of orbiting and fly-by satellites and survey instrumentation, we have now acquired cave data across our solar system-including the identification of potential cave entrances on the Moon, Mars, and at least nine other planetary bodies. These discoveries gave rise to the study of planetary caves. To help advance this field, we leveraged the expertise of an interdisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 231 publications
(395 reference statements)
0
16
0
Order By: Relevance
“…In each case, PASA or PASA-L was one component of an instrument suite, either used as a standalone instrument but in tandem with other technologies or integrated onto a single robotic platform in the case of PASA-L and LEMUR 3. As previously demonstrated in Uckert et al (2017Uckert et al ( , 2020, and reaffirmed by a broad community of planetary cave exploration experts (Wynne et al, 2022), the power of an instrument suite cannot be understated. NIR spectroscopy is a tool that can distinguish broad functional groups in mineralogical studies, which is an important contribution to our understanding of planetary subsurfaces.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In each case, PASA or PASA-L was one component of an instrument suite, either used as a standalone instrument but in tandem with other technologies or integrated onto a single robotic platform in the case of PASA-L and LEMUR 3. As previously demonstrated in Uckert et al (2017Uckert et al ( , 2020, and reaffirmed by a broad community of planetary cave exploration experts (Wynne et al, 2022), the power of an instrument suite cannot be understated. NIR spectroscopy is a tool that can distinguish broad functional groups in mineralogical studies, which is an important contribution to our understanding of planetary subsurfaces.…”
Section: Discussionmentioning
confidence: 85%
“…These techniques include (but are not limited to) mass spectrometry (Garcia‐Descalzo et al., 2012 ; Getty et al., 2012 ), Raman spectroscopy (Tarcea et al., 2007 ), X‐ray diffraction spectroscopy (Blake et al., 2012 ), imaging microscopy (Núñez et al., 2014 ), and laser induced breakdown spectroscopy (LIBS) (Pavlov et al., 2012 ; Schröder et al., 2013 ). There is general agreement that a multitude of techniques probing a range of spatial and temporal scales is needed to determine the presence of extant or extinct life on another planetary body (Boston et al., 2001 ; Cady et al., 2003 ; Conrad & Nealson, 2001 ; Wynne et al., 2022 ). Uckert et al.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, caves represent a protected habitat with reduced abiotic stressors such as high irradiance, UV/gamma radiation, desiccation, different contaminants and fast temperature variations, at the cost of limited light availability (Billi et al, 2022). On Earth, caves show high (cyano)bacterial diversity (Hauer et al, 2015;Popović et al, 2020;Prescott et al, 2022) and could represent suitable growth environments on other planetary bodies featuring relatable conditions (Wynne et al, 2021). These conditions are represented by a stable temperature regime, rough surface textures and constant as well as continuous humidity supplies provided by runoff-or seepage water (Figures 2D, E).…”
Section: Figurementioning
confidence: 99%
“…While Mars contains large and interconnected cave systems across the planet (Cushing et al, 2007;Sauro et al, 2020), the Earth's Moon is well known for its craters and lunar tubes (Chappaz et al, 2017;Kaku et al, 2017). Such pit craters, formed from the collapsed ceilings of subsurface void spaces such as natural caves or lava tubes, have been detected on almost every rock body within the inner Solar System (Wyrick et al, 2004;Haruyama et al, 2009;Davey et al, 2013;Titus et al, 2021): so far, approximately 2,660 subsurface access points have been cataloged on Solar System bodies (Titus et al, 2021), and since the discovery of the first caves on Mars, the spacecraft NASA's robotic Mars Odyssey Orbiter has helped identify over 1,000 probable gaps on the Red Planet that have been compiled into the Mars Global Cave Candidate Catalog, also known as the MGC (Cushing, 2017). Recently it has been shown that some of the lunar pits and caves provide a temperature around 17 °C with a stable and safe thermal environment for long-term exploration and habitation of the Moon (Horvath et al, 2022;Rodeghiero et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We further intimate that an opening may become characterized as a cave entrance once sufficient data supports the feature connects the surface to the deeper subsurface via a laterally trending void or cave. However, features determined not to represent a subsurface void or cave may still retain high value in planetary research as SAPs could provide much deeper access to the subsurface than current drilling technologies permit (refer to Wynne, Titus, et al., 2022).…”
Section: Processes and Productsmentioning
confidence: 99%